Partisipasi Masyarakat dalam Program Pengolahan Sampah (Studi Kasus: Pengolahan Sampah di Dukuh Serut, Desa Palbapang, Kecamatan Bantul, Kabupaten Bantul, DIY) - , Y. DHANANG M ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research on community-based waste management program in Serut and aims to determine the participation of the community or group of waste management in the waste management program is to empower the community. In addition, this study also analyzes the factors that influence participation. This research is descriptive qualitative research which intends to describe the phenomena occurring at the sites. In this study has been obtained qualitative data from multiple informants defined by purposive sampling technique, among others, Chairman of Serut, Asola group manager, Ngudi Mandiri group manager, and villagers of Serut. Data collection for the study was conducted by interview, observation and documentation in the field. From this studies, it can be concluded that community participation in communitybased waste management program in Serut still not optimal because not all people can participate fully in all stages of the waste management program. Only some groups of people are involved in the planning stages, while other people merely receive information. In the implementation phase, and the utilization of the public have been able to participate properly, the majority of citizens have applied the principles of 4R and benefit. Factors leadership and communication factors are factors that influence the community participation in waste management programs in Hamlet Serut. In connection with the discussion of the results, it can be recommended three things. First, administrators need to turn the waste management group to include the entire community and engage the government in order to run the process of selecting a neutral caretaker. Second, the government is expected to provide direct assistance and training to the community on an ongoing basis. Third, people need to reproduce the experience in the activities of local organizations outside the waste management group.